2014
DOI: 10.1073/pnas.1319142111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the 11- cis- specific retinyl-ester synthase in retinal Müller cells as multifunctional O- acyltransferase (MFAT)

Abstract: Absorption of a photon by a rhodopsin or cone-opsin pigment isomerizes its 11-cis-retinaldehyde (11-cis-RAL) chromophore to all-trans-retinaldehyde (all-trans-RAL), which dissociates after a brief period of activation. Light sensitivity is restored to the resulting apo-opsin when it recombines with another 11-cis-RAL. Conversion of all-trans-RAL to 11-cis-RAL is carried out by an enzyme pathway called the visual cycle in cells of the retinal pigment epithelium. A second visual cycle is present in Müller cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 27 publications
1
51
0
1
Order By: Relevance
“…Indeed, it was shown recently that the retina promotes pigment regeneration and dark adaptation in cones independently of the RPE, and that pharmacological ablation of Müller cells blocks this process (5). Recent biochemical studies have identified putative retinoid isomerase (7) and ester synthase activities (8) in Müller cells consistent with a retinal visual cycle. However, the molecular mechanism involved in the trafficking and recycling of chromophore still remains largely unknown, and skepticism still remains, partly due to the lack of experimental evidence for the involvement of any of the putative molecular players in this path- -/-retinae with AAV-driven expression of control GFP (black, n = 4), Müller cell-specific CRALBP (red, n = 5), and RPE-specific CRALBP (green, n = 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was shown recently that the retina promotes pigment regeneration and dark adaptation in cones independently of the RPE, and that pharmacological ablation of Müller cells blocks this process (5). Recent biochemical studies have identified putative retinoid isomerase (7) and ester synthase activities (8) in Müller cells consistent with a retinal visual cycle. However, the molecular mechanism involved in the trafficking and recycling of chromophore still remains largely unknown, and skepticism still remains, partly due to the lack of experimental evidence for the involvement of any of the putative molecular players in this path- -/-retinae with AAV-driven expression of control GFP (black, n = 4), Müller cell-specific CRALBP (red, n = 5), and RPE-specific CRALBP (green, n = 3).…”
Section: Discussionmentioning
confidence: 99%
“…The cone-specific visual cycle (3) has been suggested to enable cones, but not rods, to quickly recover from bright light exposure and to function over a wide range of light intensities (4)(5)(6). While an active area of research (7,8), to date, none of the putative molecular components in this pathway have been shown to actually affect mammalian cone function, casting doubt on the significance of this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Tissues were cryopreserved first in 10% and then 30% sucrose solutions in PBS before embedding in OCT (TissueTek) and cut into 10-m sections. Sections were prepared as described previously (4). Primary (YenZym) and secondary (Alexa Fluor 488 donkey anti-rabbit) antibodies were used at 1:100 dilutions.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Restoration of light sensitivity to the resultant apo-opsin occurs after it recombines with another 11-cis-RAL. The conversion of all-trans-RAL back to 11-cis-RAL is carried out by multistep enzyme pathways in the retinal pigment epithelium (RPE) (1) and Müller cells of the retina (2)(3)(4). Non-enzymatic photoisomerization of retinyl lipids also contributes to 11-cis-RAL synthesis and visual pigment regeneration (5).…”
mentioning
confidence: 99%
“…Electrophysiology demonstrates absent rod function but there may be residual cone function in childhood 5 10. This may reflect the alternative source of 11- cis -retinol that cones obtain from Müller cells 11. Gene therapy trials using subretinally administered recombinant adeno-associated viral vectors expressing RPE65 have so far achieved promising, although largely unsustained improvements in retinal function 12–14…”
Section: Introductionmentioning
confidence: 99%